Volatility as an asset class : diversification benefits of adding VSTOXX futures to European multi-asset portfolios - Jaatinen, Jimi (2021)
Previous research has suggested that cross correlations of different asset classes tend to increase during market downturns. This in turn leads investors to look for alterna- tive sources of diversification. Placing special emphasis on the 2020 stock market crash triggered by COVID-19, this paper examines whether there are diversification benefits in adding VSTOXX futures of different maturities to portfolios constructed from sev- eral European and global asset classes. By analyzing daily returns of VSTOXX futures and several other asset classes on period from January 2011 to December 2020, we employ finite-sample mean-variance spanning test proposed by Huberman and Kandel (1987) as well as the step-down ap- plications of Kan and Zhou (2001) to get a more precise picture of what causes the rejection or acceptance of the spanning test. Furthermore, to get robust measures under non-normality, we employ GMM Wald test and its step-down applications proposed by Kan and Zhou (2001) to control for non-normal distribution. In addition, to deter- mine the magnitude of diversification benefits, we apply two diversification measures proposed by Petrella (2005) with and without investment policy constraints to reflect realistic as well as theoretical investment choices. Our empirical results are robust and indicate that all chosen VSTOXX futures im- prove the investment opportunity set during the full period and the 2020 stock market crash. Contrary to previous research, we found that 5-month VSTOXX futures offer the most significant diversification benefits with and without investment policy con- straints during the full period and the 2020 stock market crash. This research sheds new light on the subject of volatility diversification and illustrates that it can be bene- ficial to add VSTOXX futures to European multi-asset portfolios. However, due to weak long-term performance of VSTOXX futures, a more dynamic investment strategy than holding a constant long exposure in VSTOXX is recommended.